Pengaruh Kualitas Pelayanan dan Citra Merek terhadap Kepuasan Pelanggan CV. Anugerah Mestika Abadi Event Organizer - Anggreini, Nella; Tarigan, Jenny Sari; Wardani, Alvia Rahma (Abdimas Indonesian Journal, 2024)
The event organizer industry has grown rapidly in recent years, especially after the Covid-19 period. Along with the increasing demand for various events, from small events to large events. In meeting customer satisfaction, the impact of service quality and brand image is one of the things that can influence consumers. Service quality and brand image are 2 of the many factors that influence customer satisfaction. The purpose of this study is to determine the effect of service quality and brand image on customer satisfaction. This study uses a quantitative research method with data collection carried out through questionnaires and literature studies. The data results were analyzed using data quality tests, classical assumption tests, multiple linear analysis, determination coefficient tests and hypothesis tests with 31 respondents. The results of this research show that service quality and brand image partially and simultaneously have a positive and significant effect on customer satisfaction. The brand image variable has the most dominant influence, followed by the service quality variable. The coefficient of determination value of 0.822 indicates that 82.2% of service quality and brand image influence customer satisfaction, while 17.8% is influenced by other factors not examined in this research.